Analysis of the 3' flanking region of the human c-myc gene in lymphomas with the t(8;22) and t(2;8) chromosomal translocations. - Sun, L K (1986)
We have cloned and mapped the sequences extending 38 kb 3' of the c-myc gene. This region is found to be highly repetitive in nature and hybridizes extensively with a BLUR 8 Alu probe. Unique sequence probes derived from this region were used to map the chromosomal breakpoints of a number of lymphoma cell lines with t(2;8) or t(8;22) translocations. In five of the cell lines (PA682, LY67, LY47, LY66 and LY91), the immunoglobulin light chain locus translocates into a region which is greater than 47 kb downstream of c-myc. For one of the cell lines, JI, the location of the breakpoint on the 8q+ chromosome was found to be 25-32 kb 3' of c-myc. The breakpoint for the BL2 cell line had been previously mapped at 10 kb 3' of the c-myc oncogene. Analyses of steady-state levels of c-myc mRNA in cell lines with chromosomal breakpoints ranging from 10 kb to greater than 47 kb 3' of c-myc range from 0.5 to 10X the levels in lymphoblast controls. The different levels of c-myc transcripts is not a direct function of the distance between the c-myc gene and the translocated immunoglobulin light chain locus.